Foyle's war. A lesson in murder Set 1, part 3 [videorecording (DVD)] - Thacker, David; Kitchen, Michael; Howell, Anthony, 1971-; Weeks, Honeysuckle, 1979-; Ovenden, Julian (Acorn Media, 2003)
A conscientious objector dies in police custody, setting in motion a series of suspicious deaths and a complicated puzzle for Foyle.